Freedom of Speech in parliament: Constitutional safeguard or sword of oppression? - Best, Richard (Victoria University of Wellington Law Review, 1994)
This article explores the role and the abuse of the privilege of freedom of speech in Parliament. Some unfortunate consequences of the Court of Appeal decision in TVNZ v Prebble are examined, especially in the light of Article 9 of the Bill of Rights 1688 and the New Zealand Bill of Rights Act 1990. Avenues for reform of parliamentary privilege are addressed.